Digital skills of people with disabilities studying during the pandemic – in the perspective of survey research at the University of Warsaw - Giermanowska, Ewa; Izdebski, Albert (Inclusive Digital Technologies: Perspectives, Opportunities, and Limitations, 2025)
Te pandemic period forced a change in social behavior and the operating conditions of manyorganizations, including universities. Te need to limit direct interactions caused basic activities– in most cases – such as education and work to move to the digital reality.Te impact of the pandemic on the conditions of education and the functioning of students hasbeen addressed in many empirical studies. In this article, we want to focus on the analysis of selectedaspects related to the remote form of learning at universities, mediated by digital media.Te aim of the article is to compare the digital skills of female and male students with disabilitiesto other students studying during the pandemic at the University of Warsaw. Te topics discussedinclude the possibilities of using hardware and sofware for distance learning, skills and self-assessmentof conditions for distance learning, and participation in training.Te presented opinions of the respondents on the availability of the necessary equipment for remotelearning and the ability to use sofware allow us to determine the situation of students (withand without disabilities) during the period of compulsory remote learning caused by the pandemic.Te article uses the results of a survey: „Studies in the feld of remote technologies – education atthe University of Warsaw in the era of the pandemic” conducted in 2021.